The View of Educational Institutions Managers on SIIIR - Claudia Tatiana MUNTEAN (Revista de Management Comparat International)
The contemporary pre-university education, especially in Romania, is characterized by rapid and profound changes that require continuous improvement of management and educational performance in pre-university educational institutions. Educational institutions are forced to adapt and acquire appropriate to meet these challenges. In this context choosing and implementing solutions that provide access to better services, aligning technology resources with institutional missions and increasing the value of institutional data is imperative. SIIIR = Integrated Information System for Education in Romania This system aims to provide full management services activities undergraduate educational system in terms of operational, technical, administrative and strategic. It addresses both the needs of users at central level and locally identified needs (the school level). SIIIR implementation is part of a project entitled "Integrated Information System Education in Romania", financed from the European Social Fund Operational Program Administrative Capacity Development 2007-2013. This project beneficiary is the Ministry of National Education - Projects Management Unit ExternalFinancing. Project context (as specified in course support appeared in May 2014) is as follows: "The Ministry of National Education, the central authority that coordinates national education system, has a set of information, databases and primary tools for analysis and control unintegrated . SIIIR is offering MEN support to increase capacity planning and monitoring the Romanian educational system, which will ensure increased capacity of Romania to compete long-term global market of goods and services."